Anticandidal activity of green synthesised silver nanoparticles and extract loaded chitosan nanoparticles of Euphorbia prostata. Issue 1 (31st December 2022) - Dzoyem, Jean P.; Tchuenguem, Roland T.; Iqbal, Jamshed; Yameen, Muhammad Arfat; Mannan, Abdul; Shahzadi, Irum; Ismail, Tariq; Fatima, Nighat; Murtaza, Ghulam
Abstract: This study aimed to synthesize the silver nanoparticles (SNPs) and loaded chitosan nanoparticles (LCNPs) using Euphorbia prostata based on their anticandidal activity. Antioxidant capacity and the total phenolic and total flavonoid content of plant samples and synthesized nanoparticles (NPs) were also evaluated. SNPs and LCNPs were prepared, respectively using chemical reduction of silver salt solution and ionotropic gelation method. The anticandidal activity was assessed by broth micro-dilution method and the antioxidant activity was determined using free-radical scavenging assays. The synthesized NPs after the optimization process were found to be spherical with sizes ranging from 12 to 100 nm. Spectroscopic analysis of NPs showed the appearance of peaks in prescribed wavelength ranging between 402 and 493 nm. The synthesized NPs showed potent anticandidal activity compared to the free extract. The SNPs formulations NpEPM 7.5 and NpEPMR 7.5, showed significantly low MIC values ranging between 2 and 128 µg/mL. In the case of LCNPs, NpEPM (4:1) and NpEPME (4:1) also showed lower MIC values ranging from 32 to 256 µg/mL. The plant samples as well as NPs showed antioxidant potential. In addition, plant extracts and NPs possess the potent biological potential and can be further investigated through in vivo experiments.